New Product Development Strategy for Sustainable Rigid Plastic Packaging at XYZ Company in 2022-2025 - Bernhard Eko Hendrasetyawan; Erlinda Nusron Yunus (School of Business, IPB University (SB-IPB), 2022)
This study developed environmentally friendly products for XYZ Company through business strategy analysis, macro external environment analysis, industry analysis, the voice of customer analysis, functional analysis, canoe model integration and quality functional deployment, and cost-benefit analysis. Based on the analysis results, a new product development strategy for sustainable rigid plastic packaging was formulated at XYZ Company in 2022-2025. The formulation of a new product development strategy at XYZ Company began by collecting data from XYZ Company's Business Strategy, analyzing internal factors using functional analysis, and analyzing the external environment (regulations, economic, social, political conditions, industry pressures, and results of customer interviews with XYZ Company) with using PESTEL Analysis, Industry Analysis (Five Forces Porter), and Voice of Customer Analysis. All data were combined in the Kano model matrix and Quality Function Deployment Matrix, which produced new product characteristics that will become the basis for XYZ Company in designing new products, conducting cost and benefit analysis, and determining strategy formulation. Based on the analysis results, XYZ Company could develop a 20L Jerrycan product for refillable packaging with Post-Consumer Resin (PCR) Material, using Extrusion Blow Molding and Injection Molding Process, and collaborating with customers to develop product cycles for refillable packaging offered to customers. The XYZ Company's effective New Product Development Strategy for sustainable plastic packaging in 2022-2025 is manufacturing refillable packaging with PCR material and using existing machines. Keywords: product development, kano model, quality functional deployment, sustainability, rigid plastic packaging